A SARS-CoV-2 familial cluster infection reveals asymptomatic transmission to children. Issue 6 (June 2020) - Chen, Ming; Fan, Panpan; Liu, Zhi; Pan, Rui; Huang, Shaowu; Li, Junhua; Zhao, Dongchi
Abstract: Information on SARS-CoV-2 asymptomatic infection and infectivity in children is limited. In this study, we aimed to report the epidemiological and clinical characteristics of a familial cluster infection including children with SARS-CoV-2. On February 1, 2020, two children(case 1 and case 2), an 8-year-old girl and a 9-year-old boy, were admitted to the isolation ward in Xiangyang Central Hospital, Hubei province, China, with the diagnosis of COVID-19. Before admission, they had been staying at home with their father and never contacted with any confirmed patients except their mother (case 3) who returned from Wuhan on January 22. Both case 1 and case 2 got mild symptoms. Case 3 did not develop any symptoms until February 6, 2020, with an asymptomatic period of 15 days. She was transferred to ICU and administered multiple treatment according to the disease progression and chest CT manifestations. Her nucleic acid test turned positive until Feb 21, 2020, 15 days after symptoms onset, 30 days after her return from Wuhan. Our data showed that patients with SARS-CoV-2 may have the ability to transmit during their asymptomatic period even with the negative of viral nucleic acid in pharyngeal swabs.